Degrading and Non-Degrading Sex in Popular Music: A Content Analysis - Primack, Brian A. (Association of Schools of Public Health, 2008)
OBJECTIVES. Those exposed to more degrading sexual references in popular music are more likely to initiate intercourse at a younger age. The purpose of this study was to perform a content analysis of contemporary popular music with particular attention paid to the prevalence of degrading and non--degrading sexual references. We also aimed to determine if sexual references of each subtype were associated with other song characteristics and/or content. METHODS. We used Billboard magazine to identify the top popular songs in 2005. Two independent coders each analyzed all of these songs (n=279) for degrading and non-degrading sexual references. As measured with Cohen's kappa scores, inter-rater agreement on degrading vs. non-degrading sex was substantial. Mentions of substance use, violence, and weapon carrying were also coded. RESULTS. Of the 279 songs identified, 103 (36.9%) contained references to sexual activity. Songs with references to degrading sex were more common than songs with references to non-degrading sex (67 [65.0%] vs. 36 [35.0%], p<0.001). Songs with degrading sex were most commonly Rap (64.2%), whereas songs with non-degrading sex were most likely Country (44.5%) or Rhythm & Blues/Hip-Hop (27.8%). Compared with songs that had no mention of sexual activity, songs with degrading sex were more likely to contain references to substance use, violence, and weapon carrying. Songs with non-degrading sex were no more likely to mention these other risk behaviors. CONCLUSIONS. References to sexual activity are common in popular music, and degrading sexual references are more prevalent than non-degrading references. References to degrading sex also frequently appear with references to other risky behaviors.